Student-teacher agreement on personality traits and social competencies during early adolescence: A longitudinal study - Marek Blatný; Veronika Koutná; Martin Jelínek; Petr Květon; Alexander T. Vazsonyi (PLoS ONE, 2026)
The present study sought to validate existing knowledge on inter-rater agreement on personality traits and social competencies. Based on longitudinal data, the study aimed to determine whether the agreement between student and teacher reports changes over time. The research sample consisted of a total of 296 early adolescents (181 females, 115 males, average age in the first wave of the two-year study period was 12.37 years). The personality traits and social competencies of students were rated by class teachers (N = 28, 75% females). Personality traits were measured by the Big Five Inventory and social competencies by the Social Skills Improvement System. The main findings of the study are as follows: 1) the highest agreement between student and teacher ratings of personality traits and social competencies was found for characteristics that were high in observability; 2) there was greater agreement between student and teacher ratings of social competencies for girls; 3) high temporal stability was found for personality traits and social competencies for both students and teachers; there were no substantial changes in the agreement of student and teacher ratings over time. Attention to hidden or difficult-to-assess student characteristics may prevent developmental, school, and social/interpersonal problems in adolescents.